ANALISIS JATUH TEGANGAN DAN PERBAIKANNYA PADA JARINGAN DISTRIBUSI TEGANGAN MENENGAH DI GI SUKOREJO - Ifah Dea Hapsyari; Teguh Utomo; Rini Nur Hasanah (Jurnal Mahasiswa TEUB, 2022)
In order to meet the electricity demand, we need to build a reliable distribution system. However, studies found that providing a service without interruption is challenging, especially avoiding voltage drop interruption remains a difficult task. Although voltage drop interruption is ineluctable, the distribution system usually can tolerate it at a certain level or threshold. Based on the regulation standard by the Ministry of Energy and Mineral Resources of Indonesia in 2009, the safe thresholds are between -10% to +5% of the standard value. As a part of the maintenance procedure, an engineer must ensure that an electrical power distribution system follows those rules to avoid voltage drop interruptions. This study observed the power flow of four connected feeders (Buluagung, Glagah Sari, Tutur, and Kayoman) at the Sukorejo main substation. The electrical power flow of each feeder fluctuated as follows: for Buluagung, the maximum voltage drop was 4.85%, Glagah Sari was 6.65%, Tutur was 2.59%, and Kayoman was 18.89%. Kayoman had te highest voltage drop, and the value passed the defined standard from the Ministry. Thus, this study proposed a framework to reduce the voltage drop value in Kayoman by adding a capacitor bank by analyzing the loss sensitivity along with the norm method. This study performed eight simulations and simulation number four, with additional capacitor installation on buses 8, 9, 12, and 16, giving the optimal result as the voltage drop value reduced to 8.71% for Kayoman. The real and reactive power losses were 934.43 kW and 1,303.54kVAR, respectively.Keywords: distribution system, loss-sensitivity analysis, reactive power difference, voltage drop